The threat of pesticide and disease co-exposure to managed and wild bee larvae. (April 2022) - Yordanova, Monika; Evison, Sophie E.F.; Gill, Richard J.; Graystock, Peter
Abstract: Brood diseases and pesticides can reduce the survival of bee larvae, reduce bee populations, and negatively influence ecosystem biodiversity. However, major gaps persist in our knowledge regarding the routes and implications of co-exposure to these stressors in managed and wild bee brood. In this review, we evaluate the likelihood for co-exposure to brood pathogen and pesticide stressors by examining the routes of potential co-exposure and the possibility for pollen and nectar contaminated with pathogens and pesticides to become integrated into brood food. Furthermore, we highlight ways in which pesticides may increase brood disease morbidity directly, through manipulating host immunity, and indirectly through disrupting microbial communities in the guts of larvae, or compromising brood care provided by adult bees. Lastly, we quantify the brood research bias towards Apis species and discuss the implications the bias has on brood disease and pesticide risk assessment in wild bee communities. We advise that future studies should place a higher emphasis on evaluating bee brood afflictions and their interactions with commonly encountered stressors, especially in wild bee species. Highlights: Brood exposure to pathogens and pesticides may occur frequently and in combination during the consumption of pollen and nectar. Brood pathogen virulence can be directly increased due to pesticide-mediated manipulation of larvae immune responses. Pesticides may indirectly increase brood disease morbidity by affecting larval gut microbial compositionand adult bee health. Research bias towards Apis species skews our understanding and management of brood disease and pesticide risks in wild bees.